2020
DOI: 10.18203/2394-6040.ijcmph20202506
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of occupational ocular injury in a tertiary eye care centre of North India

Abstract: Background: Occupational ocular injuries are quite common among industrial and agricultural workers. It is an important cause of preventable vision loss in developing as well as developed countries. The principal objective of our research work was to study epidemiological profile of occupational ocular injuries and use of protective eye wear at workplace in North India.Methods: A prospective, hospital based observational study was conducted on 400 patients of occupational ocular injuries attending emergency se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Overall, the study found the pooled prevalence of reported ocular protection practice among welders in sub-Saharan Africa to be 53.71% (95% CI: 42.54, 64.88). This is similar to the results obtained in a study conducted in North India by Dahiya who found the prevalence of eye injury among welders to be 52.97% ( 38 ). However, the prevalence of this study finding was lower compared to 75.0% by Prabhu in South India ( 39 ), and 61.9% by Wang in Taiwan ( 40 ).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the study found the pooled prevalence of reported ocular protection practice among welders in sub-Saharan Africa to be 53.71% (95% CI: 42.54, 64.88). This is similar to the results obtained in a study conducted in North India by Dahiya who found the prevalence of eye injury among welders to be 52.97% ( 38 ). However, the prevalence of this study finding was lower compared to 75.0% by Prabhu in South India ( 39 ), and 61.9% by Wang in Taiwan ( 40 ).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the study found the pooled prevalence of reported ocular protection practice among welders in sub-Saharan Africa to be 53.71% (95% CI: 42.54, 64.88). This is similar to the results obtained in a study conducted in North India by Dahiya who found the prevalence of eye injury among welders to be 52.97% (38). However, the prevalence of this study finding was lower compared to 75.0% by Prabhu in South India (39), and 61.9% by Wang in Taiwan (40).…”
Section: Discussionsupporting
confidence: 89%
“…Repeated eye injuries elevate the likelihood of enduring visual impairment elevate the likelihood of enduring vision impairment [4,5]. Workrelated eye injuries are more common and severe in developing nations such as India due to the lack of emphasis on occupational health and workplace safety [6]. Literature has revealed that work-related eye injuries make up 22% of all ocular trauma cases in their study on ocular trauma [7].…”
Section: Introductionmentioning
confidence: 99%